Efficient Design of Variation-Resilient Ultra-Low Energy Digital Processors - Reyserhove, Hans.; Dehaene, Wim.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book enables readers to achieve ultra-low energy digital system performance. The author's main focus is the energy consumption of microcontroller architectures in digital (sub)-systems. The book covers a broad range of topics extensively: from circuits through design strategy to system architectures. The result is a set of techniques and a context to realize minimum energy digital systems. Several prototype silicon implementations are discussed, which put the proposed techniques to the test. The achieved results demonstrate an extraordinary combination of variation-resilience, high speed performance and ultra-low energy. Presents a full bottom-up micro-electronics approach: circuit-level, design strategy and CAD automation, architecture optimization Motivates discussion with simulation results and/or measurements in an advanced nanometer CMOS process Compares traditional circuit/design/architecture techniques and state-of-the-art, setting the landscape of current best performance and how it can be improved.
Chapter 1. Energy-Efficient Processors: Challenges and Solutions -- Chapter 2. Near-Threshold Operation: Technology, Building Blocks and Architecture -- Chapter 3. Efficient VLSI Design Flow -- Chapter 4. Ultra-Low Voltage Microcontrollers -- Chapter 5. Error Detection and Correction -- Chapter 6. Timing Error-Aware Microcontroller -- Chapter 7. Conclusion.
Keywords: Electronic circuits; Signal processing; Electronics; Electronic Circuits and Systems; Signal, Speech and Image Processing; Electronics and Microelectronics, Instrumentation